Mathematical model of energy saving glass coating shape design using binary harmony search for better signal transmission - Jasmi, Muhammad Izzuddin (2017)
In recent years, buildings are designed using a special coated glass window. This glass serves as the outer shell that avoids the exposure of dangerous Ultra-violet rays; hazard light, direct sunlight and heat. Instead of being a normal window, this glass also acts to maintain the internal temperature of a building. Besides, this glass is known with the ability to save energy, which is an extensive technology of low-emissivity glasses that assist in reducing electricity usage. However, the use of this glass has impacted signal transmissions such as electromagnetic signal use in mobile communication by causing attenuation to the useful signals such as mobile phone (GSM, 3G), global positioning system (GPS), wireless network (Wi-Fi) and wireless broadband (LTE) due to the fabricated layer made of metallic-oxide on the window. Thus, engraving approach using a symmetrical shape design on the surface layer has shown improvement in reducing the attenuation problem. A well-designed algorithm is able to generate an optimized irregular shape design that can result in less attenuation on the transmission signal. Therefore, this study was conducted to propose a practical and effective irregular shape design that considers the property of coated layer and transmission signal. This approach is able to provide less attenuation problem and high efficiency of the signals through the coated glass. A model was developed to specify the requirement of coated glass on the energy saving glass. It determines the optimum irregular shape design, which is then integrated with Harmony Search (HS) optimization technique. By applying HS, an optimized shape design was generated, which met the objective of this study. HS generates a binary design representing bit ‘1’ and ‘0’. The obtained result were then simulated into a CST (Microwave) and tested on the S-parameter aspects, which are the return loss (S11) and transmission coefficient (S21). The efficiency of the irregular shape design was attained after the simulation process. Meanwhile, experimental result obtained in this study showed an irregular shape design generated by HS, hence showing an improvement in reducing the attenuation problem by 99.88% efficiency. The coated glass with optimized irregular shape design engraved on it can give a better signal transmission for mobile device, tracking system, wireless network and wireless broadband.